A Fuzzy-Set Approach to Buckling Analysis of Composite Structures - Piotr Zenon Kędziora (Engineering Transactions, 2006)
A fuzzy-set approach conjugated with finite element analysis is used to investigate the influence of the variability (random field) of geometric and material properties on buckling loads understood as one of possible failure modes for composite structures. The uncertainty (the scatter) of buckling loads is created by the prescribed variations of thickness and in Young's and Kirchhoff's moduli. The a-cut and vertex methods are utilized to study the sensitivity of buckling loads to fuzzy parameters variations. Numerical results are presented for axially compressed angle ply-plates and shallow cylindrical panels.